Improving Ambulatory Health Care Proxy Completion Rates: Implementing an Interdisciplinary Clinic-Based Process. (December 2020) - Sokol-Hessner, Lauge; Allen, Griffen; Cluett, Jennifer
All adults should complete a health care proxy (HCP), especially those who are seriously ill or otherwise at increased risk of losing capacity. This study describes the implementation of an interdisciplinary process for helping patients complete HCPs during nonurgent visits at a large urban academic primary care practice between July 2014 and May 2017. The process was mapped using direct observations. Pre- and post-implementation measurement of the percent of patients who completed HCPs during their visit revealed significant improvement (1.4% vs 26.1% in the North Suite, special cause variation). Over the study period, the percentage of patients with HCP information rose significantly across the entire clinic (eg, 37% to 80% in the North Suite, Fisher exact test P < .0001; similar findings in other suites). Key facilitators and barriers to implementation were identified by physician leaders. An interdisciplinary process can sustainably improve the percentage of primary care patients with a completed HCP.